2009
DOI: 10.1021/ma8021234
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of the Plasticizing Effects of Glycerol and PEG 400 on Chitosan Films Using Solid-State NMR Spectroscopy

Abstract: Differences were found in the plasticizing effects of two commonly used softening materials on amorphous chitosan films. The plasticizing efficiencies for glycerol and PEG 400 were found to be similar in mechanical tests, but the changes in the three-dimensional H-bonded structure monitored by solid-state NMR spectroscopy were different. The analysis of Lee-Goldburg cross-polarization build-up curves demonstrated that, while glycerol decreases the mobility of the acetamide groups, PEG 400 increases it. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(95 citation statements)
references
References 42 publications
4
91
0
Order By: Relevance
“…They found that the two plasticizers were similar in mechanical tests, but different in the three-dimensional (3D) H-bonded structure, monitored by solid-state NMR spectroscopy. Their findings were supported by density functional theory calculations indicating formation of three H-bonds for glycerol with chitosan, and only one for PEG 400 [8]. In another study, it was found that hydrogen bonding played an important role in plasticizing starch films by monosaccharides and polyols, as indicated by FTIR spectra [9].…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…They found that the two plasticizers were similar in mechanical tests, but different in the three-dimensional (3D) H-bonded structure, monitored by solid-state NMR spectroscopy. Their findings were supported by density functional theory calculations indicating formation of three H-bonds for glycerol with chitosan, and only one for PEG 400 [8]. In another study, it was found that hydrogen bonding played an important role in plasticizing starch films by monosaccharides and polyols, as indicated by FTIR spectra [9].…”
Section: Introductionmentioning
confidence: 70%
“…They confirmed the existence of hydrogen bonds between IBP and EC using Infrared spectroscopy [7]. Domjan et al [8] determined the plasticizing efficiencies for glycerol and PEG 400 as softening materials in amorphous chitosan films. They found that the two plasticizers were similar in mechanical tests, but different in the three-dimensional (3D) H-bonded structure, monitored by solid-state NMR spectroscopy.…”
Section: Introductionmentioning
confidence: 91%
“…The adhesive showed good bond strength that could be further improved with the addition of glycerol and trisodium citrate dehydrate [79]. It has been reported that citric acid reacts with chitosan amine groups to form amide bonds [80] and glycerol acts as a plasticizer which takes part in the curing process [81]. However, all formulations were found to have poor water resistance.…”
Section: Chitosanmentioning
confidence: 99%
“…During external plasticization, only weak second-order bonds develop between the plasticizer and the polymer, while internal plasticizers are covalently bound to the plasticized material. External plasticizers can migrate in the polymer, which may lead to recrystallization of the material and loss of elasticity (37).…”
Section: Mechanical Propertiesmentioning
confidence: 99%